HARRY POTTER" AND MORAL VALUES LEARNING: A QUALITATIVE STUDY OF THE RESPONSE OF CHILDREN AGED 11-13 YEARS AGAINST J.K. ROWLING BOOKS - Ratna Setyowati Putri; Rosma indriana Purba; Donna Imelda (Dinasti International Journal of Education Management And Social Science, 2020)
"Harry Potter" and Moral Value Learning ??is a qualitative study of the response of students aged 11-13 at an international Christian school in Bekasi, Indonesia, towards the phenomenal J.K Rowling text. Through the hermeneutic method, this research tried to seek the influence of Harry Potter texts, which are suspected of bringing adverse effects for their young readers. Besides, this research offers rational considerations to the authority in schools, especially regarding matters related to book censorship. Three things investigated in this study were the ability of students to think critically in making a distinction between fiction and facts in the Harry Potter text, the influence of the Harry Potter text on students' tendencies of violence and occultism, and finally about student learning of moral values ??contained in the text. The data was collected through in-depth interviews with two male respondents and three female respondents aged 11-13 years with a high religious background, mediocre, and less significant religious background. It was found that all respondents were able to distinguish between fiction and facts in the Harry Potter texts, and there was no significant evidence that the texts influenced respondents' tendency for violence nor respondents' interest in occultism. This study also found that respondents were able to identify the moral values ??contained in the text.